Concussion Incidence and Recovery Among Youth Athletes With ADHD Taking Stimulant-Based Therapy. Issue 10 (8th October 2021) - Ali, Muhammad; Dreher, Nickolas; Hannah, Theodore; Li, Adam; Asghar, Nek; Spiera, Zachary; Marayati, Naoum Fares; Durbin, John; Gometz, Alex; Lovell, Mark; Choudhri, Tanvir
Background: Attention deficit hyperactivity disorder (ADHD) may affect concussion risk and recovery in youth athletes. Purpose: To evaluate the association between incidence of concussion and postinjury recovery of symptoms and neurocognitive dysfunction among youth athletes with ADHD and differential stimulant use. Study Design: Cohort study; Level of evidence, 3. Methods: From 2009 to 2019, the authors administered the Immediate Post-concussion Assessment and Cognitive Testing (ImPACT) to youth athletes at the beginning of each season. Throughout the season, athletes with concussions were examined and readministered the ImPACT both postinjury and again 7 days after the postinjury administration. These athletes (N = 7453) were divided into those with ADHD on stimulant-based therapy (ADHD+meds; n = 167), those with ADHD not on stimulant-based therapy (ADHD-only; n = 354), and those with no ADHD (non-ADHD; n = 6932). Recovery of neurocognitive dysfunction at postinjury and follow-up was calculated using the ImPACT symptom score, verbal memory, visual memory, visual motor skills, and reaction time (calculated as standardized deviations from baseline). Univariate results were confirmed with multivariate analysis. Results: The ADHD+meds cohort had a lower incidence of concussion (37.3 concussions per 100 patient-years) compared with the ADHD-only group (57.0 concussions per 100 patient-years) (odds ratio [OR], 0.51 [95% CI, 0.37-0.71]; P < .0001) and non-ADHD group (52.8 concussions per 100 patient-years) (OR, 0.50 [95% CI, 0.37-0.67]; P < .0001). At postinjury, ImPACT scores were elevated from baseline to a similar extent in the ADHD+meds cohort compared with the other 2 groups. By follow-up, however, deviations from baseline were lower among the ADHD+meds group compared with the non-ADHD group in verbal memory (OR, 0.46 [95% CI, 0.28-0.76]; P = .002), visual memory (OR, 0.27 [95% CI, 0.10-0.66]; P = .005), and visual motor skills (OR, 0.58 [95% CI, 0.33-0.99]; P = .048). The deviation at follow-up was also lower among the ADHD+meds group compared with the ADHD-only group in visual memory (OR, 0.56 [95% CI, 0.33-0.96]; P = .04) and visual motor skills (OR, 0.42 [95% CI, 0.22-0.81]; P = .01). Conclusion: Stimulant use among youth athletes with ADHD was independently associated with reduced incidence for concussion and lower deviation from baseline in verbal memory, visual memory, and visual motor skills at 7 days postconcussion, suggesting lower neurocognitive impairment at follow-up in this group versus their peers.